The maturational process of the auditory system in the first year of life characterized by brainstem auditory evoked potentials - Raquel Beltrão Amorim; Raquel Sampaio Agostinho-Pesse; Kátia de Freitas Alvarenga (University of São Paulo, 2009)
The study of brainstem auditory evoked potentials (BAEP) allows obtaining the electrophysiological activity generated in the cochlear nerve to the inferior colliculus. In the first months of life, a period of greater neuronal plasticity, important changes are observed in the absolute latency and inter-peak intervals of BAEP, which occur up to the completion of the maturational process, around 18 months of life in full-term newborns, when the response is similar to that of adults. OBJECTIVE: The goal of this study was to establish normal values of absolute latencies for waves I, III and V and inter-peak intervals I-III, III-V and I-V of the BAEP performed in full-term infants attending the Infant Hearing Health Program of the Speech-Language Pathology and Audiology Course at Bauru School of Dentistry, Brazil, with no risk history for hearing impairment. MATERIAL AND METHODS: The stimulation parameters were: rarefaction click stimulus presented by the 3ª insertion phone, intensity of 80 dBnHL and a rate of 21.1 c/s, band-pass filter of 30 and 3,000 Hz and average of 2,000 stimuli. A sample of 86 infants was first divided according to their gestational age in preterm (n=12) and full-term (n=74), and then according to their chronological age in three periods: P1: 0 to 29 days (n=46), P2: 30 days to 5 months 29 days (n=28) and P3: above 6 months (n= 12). RESULTS: The absolute latency of wave I was similar to that of adults, generally in the 1st month of life, demonstrating a complete process maturity of the auditory nerve. For waves III and V, there was a gradual decrease of absolute latencies with age, characterizing the maturation of axons and synaptic mechanisms in the brainstem level. CONCLUSION: Age proved to be a determining factor in the absolute latency of the BAEP components, especially those generated in the brainstem, in the first year of life.